2008
DOI: 10.1653/0015-4040(2008)91[249:pobtha]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Bemisia tabaci (Hemiptera: Aleyrodidae) on Healthy andCotton Leaf Curl VirusInfected Cotton

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Particularly, shortening of the vector lifespan was observed in both the immature and adult stages. Previously, reduction of adult longevity was reported in B. tabaci infected by TYLCV or Cotton leaf curl virus (CLCuV) (Rubinstein and Czosnek, 1997;Mann et al, 2008;Sidhu et al, 2009). Similar effects of plant viruses have also been reported in other insects.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, shortening of the vector lifespan was observed in both the immature and adult stages. Previously, reduction of adult longevity was reported in B. tabaci infected by TYLCV or Cotton leaf curl virus (CLCuV) (Rubinstein and Czosnek, 1997;Mann et al, 2008;Sidhu et al, 2009). Similar effects of plant viruses have also been reported in other insects.…”
Section: Discussionmentioning
confidence: 99%
“…A population of the invasive tobacco whitefly, Bemisiatabaci , fed for 56 d on tobacco plants infected with Tomato yellow leaf curl China virus (TYLCCNV) or Tobacco curly shoot virus (TbCSV) increased faster in size, had 11–17 times higher fecundity, and a 5–6 times longer lifespan [15]. Conversely, the same insect fed on Cotton leaf curl virus -infected cotton leaves lived shorter lives and laid fewer eggs [16,17]. However, these previous studies did not analyze the causal factors of the changes in vector performance: the direct impact from insect viral infection and the indirect impact from virus-induced compositional changes in the diseased plants.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Jiu et al (2007) the asymmetry between the two biotypes was expressed in a totally different manner: infection of host plant by a begomovirus, either TYLCCNV + DNAβ or TbCSV+ DNAβ, improved the performance of the B biotype substantially but had no effects on the ZHJ1 biotype. Several studies have been reported from the USA to examine the effects of virus infection of host plants on the performance of B. tabaci , although the experiments on the alien invasive B biotype and the indigenous A biotype were conducted separately (Cohen et al, 1983; Costa et al, 1991; McKenzie, 2002; McKenzie et al, 2002; Mann et al, 2008; Polton & Toapanta, 2008). These reports indicate that infection of host plants by a begomovirus may exert beneficial, neutral or negative effects on the B biotype depending on the species of viruses and host plants but usually neutral or negative effects on the A biotype.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, a number of studies have addressed the effects of virus infection of host plants on the performance of various biotypes of B. tabaci and have demonstrated a range of outcome (Colvin et al, 2006). Compared to its performance on uninfected plants, the B biotype feeding on begomovirus‐infected plants performed better (McKenzie, 2002; McKenzie et al, 2002), similarly (Lapidot et al, 2001; Mann et al, 2008), or less well (Lapidot et al, 2001; Polston & Toapanta, 2008). In addition, virus infection of the B biotype per se could reduce the whitefly's longevity and fecundity (Rubinstein & Czosnek, 1997; Jiu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%